Efektivitas Pendidikan Kesehatan Menggunakan Multimedia dalam Meningkatkan Pengetahuan Manajemen Stroke pada Lansia - Desi Holifatus Suaida; Ahmad Zaini Arif; Nurul Fatmawati; Mery Eka Yaya Fujianti (Institut Nalanda, 2026)
Stroke is a non-communicable disease that significantly contributes to disability and mortality worldwide, including in Indonesia. It occurs due to impaired blood flow to the brain, causing brain tissue damage that may result in neurological deficits, paralysis, communication problems, and reduced quality of life. This study aimed to determine the effectiveness of health education using multimedia in improving stroke management knowledge among elderly individuals. A quantitative approach with a pre-experimental one-group pre-test and post-test design was used. The study involved 33 respondents selected through simple random sampling, and data were analyzed using univariate analysis with IBM SPSS Statistics. Before receiving multimedia-based health education, most respondents had poor knowledge of stroke management, followed by moderate and good knowledge levels. After the intervention, respondents’ knowledge improved, with nearly half categorized as having good knowledge. The findings indicate that multimedia-based health education effectively increases elderly individuals’ understanding of stroke management. Knowledge improvement may be influenced by educational background, information retention, and age-related memory decline. Therefore, multimedia health education is effective in improving stroke management knowledge among elderly individuals at Ketapang Public Health Center.